2019
DOI: 10.17576/jsm-2019-4811-10
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evaluation of Landfill Leachate System and its Impact on Groundwater and Surface Water in Malaysia

Abstract: In this study, leachate collection and processing system in Ampar Tenang Closed Landfill (ATCL) and its impact on both groundwater and surface water was evaluated. Samples from three locations in leachate processing system (Collection, aeration and stabilization ponds), groundwater and surface water were collected and tested for twenty-one parameters covering nine heavy metals (Fe Correlation analysis for landfill leachate ponds, groundwater and surface water showed different patterns of relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It was indicated that each plant that acts as phytoremediation agent has its own efficiency rate in removing different pollutants. However, there are several factors that may affect the reduction percentage of contaminants, such as the type of pollutant and wastewater, treatment duration and pollutant concentration [52][53][54].…”
Section: Reduction Rate Of Codmentioning
confidence: 99%
“…It was indicated that each plant that acts as phytoremediation agent has its own efficiency rate in removing different pollutants. However, there are several factors that may affect the reduction percentage of contaminants, such as the type of pollutant and wastewater, treatment duration and pollutant concentration [52][53][54].…”
Section: Reduction Rate Of Codmentioning
confidence: 99%
“…According to the previous study conducted in Ampar Tenang Landfill site, high concentrations of heavy metals are hazardous for human health and the landfill site can cause a serious groundwater pollution within its proximity (Yusoff et al, 2013). Based on the previous study of Banch et al, (2019b), natural coagulant from palm oil mill effluent are able to reduce heavy metals in the leachate samples. concentration of COD from 50 mg l to 40 mg l over a period of 14 days (Zimmels et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The main problems associated with waste disposal sites are the production of leachate and release of harmful CH gas (Banch et al, 2020b). 4 The release of leachate from landfill in the environment is a concern due to toxic nature of leachate that can have deterioration effects on human health (Banch et al, 2019b). In addition, heavy metals present in leachate are highly toxic when their concentration exceeds the permissible limit set by the regulatory bodies limit (Shaikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates place the amount of leachate produced by Malaysia's landfills at around 3 million litres per day; however, other countries with rainfall levels comparable to Malaysia's frequently create considerably more leachate. [4]. Leachate composition depends mostly on the content making up the landfill but is mostly presented with dissolved organic-inorganic macro-components which includes high range of biochemical oxygen demand from 4000mg/L-13000 mg/L (BOD), chemical oxygen demand of 30000mg/L -60000 mg/L (COD) along with organic waste, and other toxicants like heavy metals and ammoniacal-nitrogen [5] [6].…”
Section: Introductionmentioning
confidence: 99%